Recent progress in understanding salinity tolerance in plants: Story of Na+/K+ balance and beyond. - Hussain, S.; Hussain, S.; Ali, B.; Ren, X.; Chen, X.; Li, Q.; Ahmad, N.
High salt concentrations in the growing medium can severely affect the growth and development of plants. It is imperative to understand the different components of salt-tolerant network in plants in order to produce the salt-tolerant cultivars. High-affinity potassium transporter- and myelocytomatosis proteins have been shown to play a critical role for salinity tolerance through exclusion of sodium (Na+)ions from sensitive shoot tissues in plants. Numerous genes, that limit the uptake of salts from soil and their transport throughout the plant body, adjust the ionic and osmotic balance of cells in roots and shoots. In the present review, we have tried to provide a comprehensive report of major research advances on different mechanisms regulating plant tolerance to salinity stress at proteomics, metabolomics, genomics and transcriptomics levels. Along with the role of ionic homeostasis, a major focus was given on other salinity tolerance mechanisms in plants including osmoregulation and osmo-protection, cell wall remodeling and integrity, and plant antioxidative defense. Major proteins and genes expressed under salt-stressed conditions and their role in enhancing salinity tolerance in plants are discussed as well. Moreover, this manuscript identifies and highlights the key questions on plant salinity tolerance that remain to be discussed in the future.
Keywords: ION HOMEOSTASIS; OSMO-PROTECTION; PROTEOMICS; SALINITY; STRESS SIGNALING